A noção de experiência na sociologia bourdieusiana: com e para além de Bourdieu - Moraes, Weslley Daniel Bueno (2025)
Amid debates on Pierre Bourdieu’s field theory and the criticism that its consolidation restricts sociology to the study of such spaces, this article aims to: (a) demonstrate that this theoretical framework and its investigative program do not prevent Bourdieu from exploring alternative research approaches; and (b) show that agents’ experiences constitute a relevant object for him. Through an interpretative reading that articulates the conceptual foundations of habitus with the books The Weight of the World and The Inheritors, the empirical potential of the notion of experience is emphasized. From this perspective, the discussion fosters an approach focused on examining this dimension of practice, proposing it as a Bourdieusian sociology of experience. The article’s main contribution lies in exploring the analytical possibilities of this notion, an aspect that remains largely underexplored in studies on Bourdieu’s work.